The Role of Intestinal Microflora in Anti-Inflammatory Effect of Baicalin in Mice - Jung, Myung-Ah; Jang, Se-Eun; Hong, Sung-Woon; Hana, Myung-Joo; Kim, Dong-Hyun (Biomolecules & therapeutics, 2012)
Baicalin, a main constituent of the rhizome of Scutellaria baicalensis, is metabolized to baicalein and oroxylin A in the intestine before its absorption. To understand the role of intestinal microflora in the pharmacological activities of baicalin, we investigated its anti-inflammatory effect in mice treated with and without antibiotics. Orally administered baicalin showed the anti-inflammatory effect in mice than intraperitoneally treated one, apart from intraperitoneally administered its metabolites, baicalein and oroxylin A, which potently inhibited LPS-induced inflammation. Of these metabolites, oroxylin A showed more potent anti-inflammatory effect. However, treatment with the mixture of cefadroxil, oxytetracycline and erythromycin (COE) significantly attenuated the anti-inflammatory effect of orally administered baicalin in mice. Treatment with COE also reduced intestinal bacterial fecal β-glucuronidase activity. The metabolic activity of human stools is significantly different between individuals, but neither between ages nor between male and female. Baicalin was metabolized to baicalein and oroxylin A, with metabolic activities of 1.427 ± 0.818 and 1.025 ± 0.603 pmol/min/mg wet weight, respectively. Baicalin and its metabolites also inhibited the expression of pro-inflammatory cytokines, TNF-α and IL-1β, and the activation of NF-κB in LPS-stimulated peritoneal macrophages. Of them, oroxylin A showed the most potent inhibition. Based on these findings, baicalin may be metabolized to baicalein and oroxylin A by intestinal microflora, which enhance its anti-inflammatory effect by inhibiting NF-κB activation.